Spectrum of epilepsy and electroencephalogram patterns in idic (15) syndrome. Issue 10 (11th August 2016) - Battaglia, Agatino; Bernardini, Laura; Torrente, Isabella; Novelli, Antonio; Scarselli, Gloria
Abstract : Previous reports summarized the seizure types occurring in patients with idic(15) syndrome. To better define this issue, we retrospectively analyzed the evolution of electroencephalogram findings and seizures in 35 patients with confirmed idic(15). Epilepsy occurred in 28 patients (80%), with a median age of onset of 3 years 3 months. The initial seizures were infantile spasms associated with a hypsarrhythmic electroencephalogram (nine patients), focal/generalized tonic (seven patients), or atypical absences (eight patients). High doses of oral steroids were given in all nine children with infantile spasms, with remission of seizures and resolution of electroencephalogram abnormalities. Among them, three were seizure free at the time of evaluation, but six later developed Lennox–Gastaut syndrome or Lennox–Gastaut‐like syndrome. The eight patients with atypical absences developed Lennox–Gastaut syndrome or Lennox–Gastaut‐like syndrome. Epilepsy was well controlled in 32% of the patients; satisfactorily controlled (seizures reduced >75%) in 21.4%; partially controlled (seizures reduced <50%) in 10.7%; and uncontrolled in 32%. One patient was not taking any anti‐epileptic drugs by his parents' choice. Fourteen percent were on monotherapy; whereas the other 82% were on polytherapy. Seizures stopped at a median age of 5 years 5 months. The interictal electroencephalogram showed slow/sharp waves, and/or biphasic spikes‐polyspikes, spike/wave complexes, and an excess of fast activity mainly over the fronto‐temporal areas. Epilepsy is a major clinical challenge in patients with idic(15), associated with a poor prognosis in 55%. Frontal lobe seizures are a novel finding. © 2016 Wiley Periodicals, Inc.